Centralization and Decentralization of Education Policy and Its Implementation in Education in Indonesia - Rike Wulandari; Firman; Dina Sukma (Konsultan Jurnal Ilmiah Indonesia, 2025)
The aim contained in regional government decentralization is to encourage regional independence in carrying out development in various fields. This is in line with the principle of decentralization, namely the transfer of authority from the Central Government to the Autonomous Regions to manage government affairs in their respective regions. This new managerial approach in government opens up opportunities for wider local community participation, and makes decisions taken by Regional Governments in providing public services more relevant and of better quality. Within the framework of decentralized government, decentralization in education seeks to place decision making closer to the needs of stakeholders. In this way, educational development can be more in line with regional characteristics, and community potential can be maximized. Finally, decentralization of education is expected to improve the quality and competitiveness of human resources.